2014
DOI: 10.1021/ol500718s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrroles from Terminal Alkynes, N-Sulfonyl Azides, and Alkenyl Alkyl Ethers through 1-Sulfonyl-1,2,3-triazoles

Abstract: A method for synthesis of substituted pyrroles has been developed. 1-Sulfonyl-1,2,3-triazoles generated from terminal alkynes gave α-imino rhodium carbene complexes, which when reacted with alkenyl alkyl ethers afforded substituted pyrroles. The method can be efficiently applied to a one-pot sequential reaction starting from terminal alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…More recently, we have reported that the reaction of triazoles with alkenyl alkyl ethers give rise to pyrroles through the corresponding dihydropyrroles 17. Next, we were interested in whether 1,3‐dienes can act as dipolarophiles to construct a dihydroazepine and dihydropyrrole scaffold 18…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we have reported that the reaction of triazoles with alkenyl alkyl ethers give rise to pyrroles through the corresponding dihydropyrroles 17. Next, we were interested in whether 1,3‐dienes can act as dipolarophiles to construct a dihydroazepine and dihydropyrrole scaffold 18…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively,i np ath b, the alkene undergoes cyclopropanation to give intermediates 8,f ollowedb yr ing enlargement to furnish the corresponding dihydropyrroles 7.F urthermore, Lee and co-workersa lso extended the methodology into at hreecomponent, one-pot procedure starting from the tosyl azide, terminal alkyne, and alkenyl alkyl ether. [10] Shortly thereafter,Liand co-workersreported asimilar rhodium-catalyzed reaction of N-sulfonyl-1,2,3-triazoles 1 with ketene silyl acetal to form 3,4-disubstituted 3-pyrrolin-2-ones 10 (Scheme 4). [12] The products were afforded in high yields when alkyl ketene silyl acetals (R 2 = alkyl) were employed.…”
Section: Attack By Carbon Atommentioning
confidence: 99%
“…In early 2014, the groups of Lee and Anbarasan independently reported rhodium‐catalyzed transannulations of N ‐sulfonyl‐1,2,3‐triazoles 1 with vinyl ethers to synthesize various polysubstituted pyrroles 5 (Scheme ). The reaction scope was broad, and various triazoles and alkenyl alkyl ethers could participate in the reaction.…”
Section: Reactions Of N‐sulfonyl‐123‐triazolesmentioning
confidence: 99%
“…Synthesis of pyrroles through a three component coupling of alkynes, sulfonyl azides, and enol ethers using a dual copper rhodium catalyst system proceeds through copper-catalyzed formation of the triazole followed by rhodium-catalyzed formation of the carbene complex and net [3+2] cycloaddition with the enol ether accompanied by alcohol elimination [1119]. The dual copper rhodium system was used to prepare α-amino silyl enol ethers from terminal alkynes, tosyl azide, and hydroxysilanes [1120].…”
Section: Page 129 Of 218mentioning
confidence: 99%